Re-Inventing the Fight against High Maternal Mortality among Developing Nations: A Case Study of Nigeria - Mercy Okeke, Nkechi; Mbagwu Okeke, Polycarp; Ngozi, F. Nnaji (International Journal of Psychosocial Rehabilitation, 2021)
This study aimed to determine the strategies for re-inventing the fight against high maternal mortalityamong developing nations using Nigeria as a case study. Specifically, the study ascertained the preventivemeasures for maternal mortality among pregnant women in rural communities in Nsukka local government areaof Enugu State, Nigeria. One research question was used to identify the preventive measures of maternalmortality among these women in Nsukka local government area of Enugu State, Nigeria. The survey design wasused. Data was collected using a questionnaire. A total of 108 pregnant women participated in the study. Datawere analyzed using mean and standard deviation. The study revealed that administering test, management ofpre-eclampsia, anemia, tetanus toxoid, screening infection, prompt treatment and magnesium sulfate usingskilled care at delivery, a cesarean section in case of prolonged labour, family planning counselling, and use ofessential vaccinations are noted for preventing maternal mortality. Based on the study, the followingrecommendations are made: education of women to raise their decision-making power, government and NonGovernmental Organizations should offer financial support to families to cushion the effect of maternal death,the government should establish legal law with a penalty to abolish harmful practices like FGM and childmarriage below 18 years, the government should implement the full practice of Safe Motherhood in all the ruralpoor and government should make child and maternal survival a core national and global health concern